A modified DAEM: To study the bioenergy potential of invasive Staghorn Sumac through pyrolysis, ANN, TGA, kinetic modeling, FTIR and GC–MS analysis. (1st October 2020) - Sajjad Ahmad, Muhammad; Liu, Hui; Alhumade, Hesham; Hussain Tahir, Muddasar; Çakman, Gülce; Yıldız, Ağah; Ceylan, Selim; Elkamel, Ali; Shen, Boxiong
Graphical abstract: Highlights: Bioenergy potential of Staghorn Sumac was explored using kinetics, FTIR and GCMS. Experimental and Predicted results were compared with DAEM model. Artificial Neural Network was used to validate the results obtained from DAEM. FTIR and GCMS results confirmed the bioenergy potential of invasive Staghorn Sumac. Abstract: Biomass is deemed to be an important contributor to satisfy our energy, chemicals and material requirements throughout the world. The present study aimed to study the bioenergy potential of Staghorn Sumac (SS) through modified distributed activation energy model (DAEM), kinetic models, thermogravimetric analyzer, elemental analyzer, Fourier transform infrared spectrometry (FTIR) and gas chromatography-mass spectrometry (GC–MS). Pyrolysis experiments were carried out at the different heating rates of 10, 20, 30 and 40 °C min −1 to study kinetics. The average activation energy values achieved through DAEM, KAS, FWO and Starink models were 160, 167, 169, and 168 kJ mol −1, respectively. Additionally, an Artificial Neural Network (ANN) model was equated with modified DAEM. Moreover, The composition of evolved gas compound measured by a gas chromatography coupled with mass spectroscopy showed that bio-oil mainly consisted of 82.33% acid, 6.37% aldehyde and ketone, 4.96% amid, 2.76% ester, 2.07% aromatic and alcohols, and 1.52% other groups. This study has revealed the remarkable potentials of Staghorn Sumac for clean bioenergy production.